2002
DOI: 10.1002/joc.671
|View full text |Cite
|
Sign up to set email alerts
|

A statistical–topographic model using an omnidirectional parameterization of the relief for mapping orographic rainfall

Abstract: The knowledge of rainfall patterns is a key issue for regionalization in hydroclimatic studies. In mountainous areas, the sparsity of the measurement network and the complexity of relationships between rainfall and topography make an accurate and reliable spatialization of rainfall amounts at the regional scale difficult. The purpose of this paper is to present an objective, analytical and automatic model of quantification and mapping of orographic rainfall applied to the north-eastern part of France but also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 24 publications
0
34
0
1
Order By: Relevance
“…(3) PLUVIA (Drogue et al 2002). The relief in the vicinity of a given target location is described based on a whole range of elevation statistics of neighboring DEM gridpoints, such as the mean, standard deviation and various quantiles.…”
Section: Methodsmentioning
confidence: 99%
“…(3) PLUVIA (Drogue et al 2002). The relief in the vicinity of a given target location is described based on a whole range of elevation statistics of neighboring DEM gridpoints, such as the mean, standard deviation and various quantiles.…”
Section: Methodsmentioning
confidence: 99%
“…Originally designed for mapping orographic areal rainfall amounts (Humbert et al, 1997;Drogue et al, 2002), the Pluvia model has been used in the present study to detect any statistical link between the MWRI and the relief of the area. Pluvia is based on an omnidirectional exploration of the topographical environment around each rain gauge.…”
Section: The Statistical-topographic Modelmentioning
confidence: 99%
“…Naoum and Tsanis (2003) studied the spatio-temporal rainfall characteristics on the island of Crete for a range of 12-50 yr and found that the rainfall-elevation correlation was significant. Drogue et al (2002) used an operational software called PLUVIA, which distributes point measurements of monthly, annual and climatological rainfall to regularly spaced grid cells through a multiple regression analysis of rainfall versus morpho-topographic parameters derived from a digital elevation model. According to Wotling et al (2000), a Gumbel rainfall distribution was performed by using a stepwise regression adjusted to rainfall records across Tahiti and an approximation of the pluviometric risk was provided.…”
Section: Introductionmentioning
confidence: 99%